2006
DOI: 10.1145/1143518.1143521
|View full text |Cite
|
Sign up to set email alerts
|

Physically large displays improve performance on spatial tasks

Abstract: Large wall-sized displays are becoming prevalent. Although researchers have articulated qualitative benefits of group work on large displays, little work has been done to quantify the benefits for individual users. In this article we present four experiments comparing the performance of users working on a large projected wall display to that of users working on a standard desktop monitor. In these experiments, we held the visual angle constant by adjusting the viewing distance to each of the displays. Results … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
102
1
1

Year Published

2010
2010
2020
2020

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 157 publications
(108 citation statements)
references
References 21 publications
4
102
1
1
Order By: Relevance
“…Subjects got stuck, or they were unable to remove the wheelchair away from the site of collision, more often on the PC screen than on the VR screen. Similar results were found by Tan et al 39 In the beginning of the research session subjects were allowed to practice virtual driving until they felt comfortable. In future studies, we plan to have a more structured training regimen which may help in reducing errors while driving.…”
Section: Discussionsupporting
confidence: 83%
“…Subjects got stuck, or they were unable to remove the wheelchair away from the site of collision, more often on the PC screen than on the VR screen. Similar results were found by Tan et al 39 In the beginning of the research session subjects were allowed to practice virtual driving until they felt comfortable. In future studies, we plan to have a more structured training regimen which may help in reducing errors while driving.…”
Section: Discussionsupporting
confidence: 83%
“…These sources of information could be vital for keeping track of the distance traveled and the magnitude of body rotations. The size of the display may also affect performance on spatial tasks (Tan, Gergle, Scupelli, & Pausch, 2006). In addition, the relation between motor efference and visual reafference in desktop VR is different from that in walking and, thus, may affect visual path integration.…”
Section: Limitations Of the Literaturementioning
confidence: 99%
“…Many of these parameters have been shown to impact human spatial orientation performance (Riecke, Schulte-Pelkum, & Bülthoff, 2005;Riecke et al, 2002;Tan, Gergle, Scupelli, & Pausch, 2006Tan, Gergle, Scupelli, & R.Pausch, 2005;Alfano & Michel, 1990). Moreover, Ruddle and colleagues themselves had demonstrated that replacing an HMD with a desk-top monitor reduces navigation performance in VR, indicated by increased navigation times and less accurate sense of straight-line distances (Ruddle, Payne, & Jones, 1999).…”
Section: Navigational Search Studies By Ruddle and Lesselsmentioning
confidence: 99%